Analysis of microsatellite instability markers in women with endometrial cancer - Kulig, Andrzej; Smolarz, Beata; Dec, Grażyna; Romanowicz-Makowska, Hanna (Menopause Review/Przegląd Menopauzalny, 2004)
Purpose: Microsatellite instability (MSI) play important role for the development of endometrial cancer. The aim of this study was evaluation of microsatellite instability in 10 postmenopausal women with endometrial cancer. Materials and methods: Cancer tissue and blood were obtained from the same patients. Blood samples from age matched healthy women served as control (n=25). MSI was studied at five loci containing single- or dinucleotide repeat sequences and mapping to different chromosomal locations: BAT-25 (at locus 4q12), BAT-26 (2p16), D2S123 (2p16-p21), D5S346 (5q21-q22) and D17S250 (17q11.2-q12). Results and conlusion: No differences in the MSI frequencies between blood and cancer tissue obtained from patients were detected. The microsatellite instability status was significantly higher in endometrial cancer tissue [4/10 (40%) ] compared as control [3/25 (12%)] (p<0.05). The results suggest that the microsatellite instability seems to be important in the development sporadic endometrial cancer.